KAJIAN HEADLINE DAN FOTO HEADLINE SURAT KABAR KOMPAS PERIODE SATU TAHUN PERTAMA KINERJA PEMERINTAHAN JOKO WIDODO–JUSUF KALLA - Fit Yanuar; Daesy Ekayanthi (Program studi Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas Persada Indonesia YAI, 2021)
Kompas, the Indonesian most popular newspaper, is always been a significant object in Indonesia communications research. It is said that Kompas is the barometer of Indonesia mass media. To know how Kompas set the agenda about President/VP Joko Widodo – Jusuf Kalla and/or its administration for one first year of their leadership is a far more interesting to know. This is a research about that matter. The research shows thatKompas,based on its headline,has given the agenda-setting in significant news and also in a positive valuation upon Joko Widodo-Jusuf Kalla administration in their first year leadership. But based on Kompas setting of headline photograph, the research shows that Kompas has not shown the significant number of headline photographupon Joko Widodo-Jusuf Kalla administration in their first year leadership. This research is framed by a classical communications theory named agenda-setting theory which started by Maxwell McCombs and Donald Shaw, followed by some communications scientists, which in this research focus on Everet Rogers and James Dearing’s thought. The research used a quantitatively research, by manual counting, based on the descriptive content analysis approach.